Institutional Arrangement Approach on e-Parking Innovation in Surabaya City, Indonesia - Farah Zhafirah; Erva Mutiara Hati; Ali Roziqin (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2023)
The implementation of parking in the city of Surabaya is regulated by Regional Regulation (Perda) Number 3 of 2018. The purpose of introducing e-parking or a parking meter tool is to suppress the leakage of PAD in the parking sector, control parking attendants, and facilitate convenient experiences for individuals visiting the smart city of Surabaya. The meter was introduced to measure the duration of parking and facilitate electronic payment of fees. Therefore, e-parking innovation plays a crucial role in effectively managing local revenue (PAD). This study predominantly focuses on the institutional governance system for implementing innovations in the public service sector, specifically the use of e-parking to address parking-related issues. This study employed a descriptive approach with a qualitative methodology. The subjects included the Head of Surabaya Parking UPTD, employees of Surabaya City Transportation Service, attendants of Surabaya City Hall and Tama Bungkul Surabaya parking, as well as the wallet team of Surabaya City Transportation Department. Data were collected using various techniques, namely interviews, observation, and documentation, and were subsequently analyzed through a systematic process of data reduction, presentation, and verification. The results showed the Surabaya City Transportation Service successfully implemented parking meters at several points, including City Hall and Bungkul Park. The implementation of the e-parking program in the city has been progressing well, despite encountering some challenges. These challenges have been effectively resolved, ensuring the smooth operation of the parking meter tool.